LeverAge: A European network to leverage the multi-age workforce - Deller, J.; Marcus, J.; Scheibe, S.; Truxillo, D.; Sousa, I.C. (22nd Congress of the European Association of Work and Organizational Psychology (EAWOP), 2025)
Funded in autumn 2023, the COST (“European Cooperation in Science and Technology”) Action network, LeverAge, brings together researchers and practitioners to advance the science and practice of work and aging (https://leverage-workforce.eu/). LeverAge currently has 192 participants (13% practitioners) from 132 institutions across 52 countries from all over Europe and globally. The Action is organized into five Working Groups (WGs) that bring together participants to drive scientific and societal impact: work and organizational practices for a multi-age workforce (WG 1), successful aging at work (WG 2), the integration of age-diverse workers and knowledge transfer (WG 3), aging and technology at work (W 4), and career development in later life and retirement (WG 5). The purpose of this panel presentation is: 1) Introduce COST Action LeverAge and 2) Share insights for expanding scholarly impact and practitioner engagement we gained while coordinating and administering the Action. Briefly, the latter include strategies to: a) harness the power of scholarly European networks, b) create globally inclusive collaborations, c) judiciously foster interdisciplinarity, d) actively engage practitioners, and e) creatively communicate scientific findings to practitioners and the public. We believe these insights may benefit the EAWOP community by fostering dialogue and ideas to enhance our collective scientific impact. This can be achieved by creating inclusive, interdisciplinary and pan-European coalitions of scholars and practitioners to help improve working lives and foster prosperity and wellbeing for the people of Europe. We invite EAWOP members with an interest in work and aging to join LeverAge. We encourage like-minded EAWOP members to form COST Action networks on their topics. Panel discussants include the LeverAge Action Chair (Dr. Justin Marcus), Action Vice Chair (Prof. Susanne Scheibe), Science Communication Coordinator (Dr. Ines Sousa), and WG 2 Leader (Prof. Donald Truxillo). The panel chairperson is the LeverAge Impact and Translational Coordinator, Prof. Jurgen Deller.